Epistemology of the otherness: between erklären (to explain) and verstehen (to understand) the other - Sá Martino, Luís Mauro (Folios, revista de la Facultad de Comunicaciones y Filología, 2018)
This paper highlights some relations between identity and otherness as a problem in Communication Studies, focusing in two elements: (a) the epistemological dimension of the otherness, i.e., of "explaining" it based on categories that are foreign to it; (b) the ethical dimension of such relation, in which the otherness is perceived as similar to being comprehended. Finally, the text reasons that communication, as an aesthetic process, requires both dimensions while establishing social relations based on comprehension and responsibility.